The Impact of Immigration on Child Health : Experimental Evidence from a Migration Lorrery Program - Stillman, Steven; Gibson, John; McKenzie, David (Western Economic Association International, 2015)
This paper uses a unique survey designed by the authors to compare migrant children who enter New Zealand through a random ballot with children in the home country of Tonga whose families were unsuccessful participants in the same ballots. We find that migration increases height and reduces stunting of infants and toddlers, but also increases BMI and obesity among 3- to 5-yr-olds. These impacts are quite large even though the average migrant household has been in New Zealand for less than 1 yr. Additional results suggest that these impacts occur because of dietary change rather than direct income effects.